New Therapies in the Field of Rheumatology - Gerosa, Maria; Beatrice Chighizola, Cecilia; Jakobsson, Per-Johan (Frontiers Media SA, 2020)
In recent years, the long term prognosis of patients with rheumatic disease has dramatically improved, due to the enormous advances in the understanding of the pathogenesis of these diseases that have led to the development of drugs targeting the molecules directly involved in the inflammatory response. The development of these biological drugs has radically changed the therapeutic approach of inflammatory rheumatic diseases, mainly in patients resistant to standard treatment. Also in the field of conventional therapy, many new data have confirmed the effectiveness of "old" drugs, such as hydroxychloroquine, methotrexate and azathioprine, demonstrating several additional beneficial properties for the treatment of Systemic Lupus Erythematosus (SLE), Rheumatoid Arthritis (RA) or other autoimmune diseases. Moreover, immunosuppressant developed to prevent graft rejection such as mycophenolate or tacrolimus have been demonstrated to have an important role in the treatment of rheumatic patients. Beside the well defined anti-inflammatory properties of biological and synthetic anti-rheumatic drugs, a number of additional beneficial effects have been suggested, that have been hypothesized to prevent long term complications of autoimmune diseases, such as accelerated atherosclerosis, increased cardiovascular risk and osteoporosis. This Research Topic collects new information regarding safety and effectiveness of new and old drugs for the treatment of RA, SLE, or other autoimmune diseases.